2009
DOI: 10.4049/jimmunol.0801592
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Subunit Vaccination Provides Long-Term Protective Immunity Characterized by Multifunctional CD4 Memory T Cells

Abstract: Improved vaccines capable of promoting long-term cellular immunity are urgently required for a number of diseases that remain global health problems. In the present study, we demonstrate that a tuberculosis subunit vaccine, Ag85B-ESAT-6/CAF01 (where ESAT-6 is early secreted antigenic target of 6 kDa and CAF01 is cationic adjuvant formulation 01), induces very robust memory CD4 T cell responses that are maintained at high levels for >1 year postvaccination. This long-term, vaccine-induced memory response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
347
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 378 publications
(386 citation statements)
references
References 32 publications
(35 reference statements)
30
347
3
6
Order By: Relevance
“…It has previously been shown that in mice vaccinated with BCG, the T cells are primarily effector or effector-memory T cells 6 mo after vaccination (32). In contrast we have shown that 1 y after vaccination with a fusion protein (H1) formulated in the same adjuvant used in this study, the T cells are primarily central memory T cells (33). In HIV-infected individuals, polyfunctional CD4 T cells are a characteristic feature observed in HIV controllers, and an inverse correlation has been shown with viral load, whereas noncontrollers elicit responses dominated by IFN-γ single-positive CD4 T cells (34).…”
Section: Discussioncontrasting
confidence: 47%
“…It has previously been shown that in mice vaccinated with BCG, the T cells are primarily effector or effector-memory T cells 6 mo after vaccination (32). In contrast we have shown that 1 y after vaccination with a fusion protein (H1) formulated in the same adjuvant used in this study, the T cells are primarily central memory T cells (33). In HIV-infected individuals, polyfunctional CD4 T cells are a characteristic feature observed in HIV controllers, and an inverse correlation has been shown with viral load, whereas noncontrollers elicit responses dominated by IFN-γ single-positive CD4 T cells (34).…”
Section: Discussioncontrasting
confidence: 47%
“…Cells from mice immunised with BCG and boosted with Nano-Ag85B (without HBHA) also produced multiple cytokines (75% produced three and 25% two cytokines), suggesting that nanoparticles play a major role in inducing the polyfunctional T-cell responses. Several recent studies have established a link between multifunctional memory CD4 + T cells, i.e.secreting IFN-γ, TNF-α and IL-2, and protection against MTB [29][30][31].In conclusion, we show here that targeting a TB Ag to lung epithelial surfaces by means of fusion with HBHA is an effective way of inducing mucosal and systemic immune responses, particularly for boosting BCG-induced immunity. Formulating HBHAderived hybrid proteins with nanoparticles further enhanced the immune responses and conferred a significantly improved protection against MTB infection, suggesting that this novel mucosal vaccination approach merits further studies, particularly in respect of longevity of the protection and understanding of the cellular and molecular mechanisms involved.…”
mentioning
confidence: 81%
“…These multifunctional memory CD4 T‐cells are found following vaccination or infection in animal models and in humans 24, 25, 26, 27, 28, 29. In infection models of Leishmania major and Mycobacterium tuberculosis , multifunctional CD4 T‐cells provide the most effective immune protection, and in humans they correlate with successful recovery from infection with Japanese encephalitis virus 25, 27, 29…”
Section: Cytokine Production Is Key To Cd4 T‐cell Protective Immunitymentioning
confidence: 99%